Dirichlet-type problems for n-Poisson equation in Clifford analysis. Issue 11 (24th July 2022) - Aksoy, Ümit; Okay Çelebi, A.
Abstract : Iterated Dirichlet problem, also called as Riquier or Navier problem, and polyharmonic Dirichlet problem are studied for n -Poisson equation in Clifford analysis using iterated polyharmonic Green function and polyharmonic Green-Almansi type function appropriate for the boundary conditions of the problems.